2001
DOI: 10.1080/00305364.2001.11745234
|View full text |Cite
|
Sign up to set email alerts
|

The effects on significant others of providing a hearing aid to the hearing-impaired partner

Abstract: Communication is a shared experience which can be substantially affected by hearing impairment. Significant others may experience difficulties not only in direct communication but also in personal and social relationships. The present study was designed to investigate the impact on significant others of hearing loss in a partner and the benefits that accrued from the provision of personal amplification. The results suggested that before the provision of a hearing aid significant others experienced difficulties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 5 publications
4
55
1
Order By: Relevance
“…Hétu and colleagues 105 reported that in an assessment of noise-exposed working-age adults, difficulties with communication and listening resulted in anxiety, stress, change in social activities, isolation in groups, and a negative self-image, which affected both the individual, spouse and significant others. In the same vein, Brooks and colleagues 106 found that individuals with hearing loss and their partners were both affected by communication difficulties resulting from the sensory loss. Other research has documented that among community-dwelling older married couples, hearing loss on the part of a partner increases a spouse's likelihood of poorer physical, psychological, and social well-being.…”
Section: Microsystem and Mesosytem Responses To Sensory Lossmentioning
confidence: 98%
“…Hétu and colleagues 105 reported that in an assessment of noise-exposed working-age adults, difficulties with communication and listening resulted in anxiety, stress, change in social activities, isolation in groups, and a negative self-image, which affected both the individual, spouse and significant others. In the same vein, Brooks and colleagues 106 found that individuals with hearing loss and their partners were both affected by communication difficulties resulting from the sensory loss. Other research has documented that among community-dwelling older married couples, hearing loss on the part of a partner increases a spouse's likelihood of poorer physical, psychological, and social well-being.…”
Section: Microsystem and Mesosytem Responses To Sensory Lossmentioning
confidence: 98%
“…11 Furthermore, while the prevalence of hearing loss in caregivers of adult patients is also unknown, we have heard anecdotal reports of caregivers misunderstanding hospice instructions due to hearing loss. 12,13 Furthermore, in very elderly patients and caregivers hearing loss must be taken in the context of the patient. Very elderly patients tend to have multiple chronic conditions, physical disability, diminished eyesight, and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Armero, 2001;Brooks et al, 2001;Hétu et al, 1993Hétu et al, , 1988Jones et al, 1987;Scarinci et al, 2008;Stark & Hickson, 2004;Wallhagen et al, 2004). Stephens et al (1995) found that spouses report more problems with psychosocial issues and spoken communication compared with their hearing-impaired partners.…”
Section: Sumariomentioning
confidence: 95%
“…Spouses experience numerous effects as a result of their partners' hearing impairment, including difficulties communicating with their partner in background noise, difficulties coping with the high volume of the television or radio, having to respond on behalf of their partners, and having to repeat during conversation (Brooks et al, 2001;Hétu et al, 1993Hétu et al, , 1988Scarinci et al, 2008;Stark & Hickson, 2004;Stephens et al, 1995). Younger female spouses have also reported a range of social restrictions as a result of their husbands' hearing loss, and emotional effects including increased effort, irritation, stress, and anxiety (Hétu et al, 1993).…”
Section: Sumariomentioning
confidence: 97%